Navigation-Assisted Isolated Medial Orbital Wall Fracture Reconstruction Using an U-HA/PLLA Sheet via a Transcaruncular Approach. Issue 7 (8th August 2020) - Dong, Quang Ngoc; Karino, Masaaki; Koike, Takashi; Ide, Taichi; Okuma, Satoe; Kaneko, Ichiro; Osako, Rie; Kanno, Takahiro
Abstract: Purpose : We investigated the feasibility of isolated medial orbital wall fracture reconstruction using an unsintered hydroxyapatite particles/poly L-lactide (u-HA/PLLA) sheet implant with the assistance of intraoperative navigation via the transcaruncular approach. Patients and methods : Ten consecutive patients (5 males and 5 females; mean age, 57.5 years) were included based on the clinical and imaging criteria. All patients underwent surgical treatment of the isolated medial orbital wall fracture using transcaruncular incision and the u-HA/PLLA implant under navigation. The follow-up time was greater than 6 months. Preoperative and postoperative clinical data regarding the presence of diplopia, eye motility restriction, and enophthalmos were assessed. The orbital volumes of the injured and uninjured orbit were also evaluated using computed tomography images. Results : All patients had improved ophthalmologic functional and esthetic outcomes and were successfully treated without any long-term complications arising during follow-up. There was a significant difference between the preoperative and postoperative injured orbits due to herniation of the orbital contents. Moreover, the orbital volume of the postoperative injured side following surgery was the same as that of the unaffected side, indicating that anatomically good reconstruction had been obtained. Conclusions : Surgical treatment using the transcaruncular approach and u-HA/PLLA materials with intraoperative navigation is a safe, promising, and effective technique for isolated medial orbital wall fracture reconstruction.